(untitled) (Acta Entomológica Chilena, 2022)
Based on a survey of type specimens, species of the New World hairstreak butterfly genus Ministrymon Clench are listed and first records from Chile reponed. M. azia Hewitson reaches its southwestern range extreme in xeric Coastal habitats near the Chile/Perú border (Arica). M. quebradivaga, new species, is described from quebrada habitat in the Northern Desert Biotic Province (Quebrada Vitor, Pampa Tamarugal), Tarapacá Región. This new species shares characters with two subgroups of Ministrymon and is probably a primitive relict. At least two other Lepidoptera studied to date show the pattern of distribution and endemism exhibited by Ministrymon in Chile.